The effectiveness of the use of operational health assistance funds in supporting the achievement of the antenatal care program at the X Community Health Center, Serdang Bedagai Regency - Fhidiana Sari; Fitriani Pramita Gurning; Dewi Agustina (Institute of Computer Science (IOCS), 2026)
The Health Operational Assistance (BOK) program contributes to increasing the coverage of antenatal care services in an effort to reduce maternal mortality. This study aims to determine the effectiveness of BOK fund utilization in supporting the achievement of the Antenatal Care program. This study uses a qualitative method with a case study design. Informants involved in this study were the Head of the Community Health Center, BOK Treasurer, Coordinating Midwife, and ANC Program Implementer. Research informants were determined using a purposive sampling technique. Data analysis was conducted using the Nvivo data processing application version 15. The results of the study revealed that the utilization of BOK funds in the implementation of Antenatal Care is not fully optimal. At the input stage, the realization of BOK funds for ANC has reached 100%, but the utilization of funds is not directly proportional to the achievements of the ANC program. Human resources for BOK fund management are not held by employees with a financial background. The policy for fund utilization is in accordance with technical guidelines. At the process stage, planning has been carried out systematically and structured. In the implementation, there are still obstacles, namely delays in fund disbursement. Reporting on the use of BOK funds has been running well. Monitoring has not been fully optimal. Mini-workshop evaluations have been conducted once a month. At the output stage, ANC outcomes have not reached targets due to a lack of participation from pregnant women and not all ANC activities being budgeted.